The genetic control of glabrous glume during African rice domestication - Chang, L.; Hu, M.; Ning, J.; He, W.; Gao, J.; Ndjiondjop, M.N.; Fu, Y.; Liu, F.; Sun, H.; Gu, P.; Sunc, C.; Zhu, Z. (Elsevier, 2022)
African cultivated rice, Oryza glaberrima, is characterized by its glabrous glumes. During domestication, the pubescent glumes of its wild ancestor, Oryza barthii, lost their trichomes, and in this study, we show that glabrous glume 5 (GLAG5), a WUSCHEL-like homeobox transcription factor gene on chromosome 5, is required for trichome development. DNA methylation associated with an hAT transposable element inserted in the promoter region of GLAG5 is found to reduce its expression, leading to the formation of glabrous glumes and leaves in African cultivated rice. Among 82 African cultivated rice varieties investigated in this study, 59 (approximately 71%) lines exhibit glabrous glumes and harbor the hAT transposon; however, the other 23 varieties (approximately 29%), which exhibit pubescent glumes, lack the hAT transposon, indicating that glag5 had undergone strong artificial selection. The πw/πc ratios also show the hAT transposon insertions influence the genetic diversity of an approximately 150-kb interval encompassing the GLAG5 locus. The identification of the GLAG5 gene provides new insights into the domestication of cultivated rice in Africa. We speculate that the selection of varieties with mutations in their promoter regions is an important aspect of crop domestication.